Efficacy of Disease Modifying Therapies in Progressive MS and How Immune Senescence May Explain Their Failure - Manouchehri, Navid; Salinas, Victor H.; Rabi Yeganeh, Negar; Pitt, David; Hussain, Rehana Z.; Stuve, Olaf (Frontiers in Neurology, 2022)
The advent of disease modifying therapies (DMT) in the past two decades has been the cornerstone of successful clinical management of multiple sclerosis (MS). Despite the great strides made in reducing the relapse frequency and occurrence of new signal changes on neuroimaging in patients with relapsing remitting MS (RRMS) by approved DMT, it has been challenging to demonstrate their effectiveness in non-active secondary progressive MS (SPMS) and primary progressive MS (PPMS) disease phenotypes. The dichotomy of DMT effectiveness between RRMS and progressive MS informs on distinct pathogeneses of the different MS phenotypes. Conversely, factors that render patients with progressive MS resistant to therapy are not understood. Thus far, age has emerged as the main correlate of the transition from RRMS to SPMS. Whether it is aging and age-related factors or the underlying immune senescence that qualitatively alter immune responses as the disease transitions to SPMS, that diminish DMT effectiveness, or both, is currently not known. Here, we will discuss the role of immune senescence on different arms of the immune system, and how it may explain relative DMT resistance.